Modulation of CD39 and Exogenous APT102 Correct Immune Dysfunction in Experimental Colitis and Crohn's Disease. (6th November 2019) - Robles, René J; Mukherjee, Samiran; Vuerich, Marta; Xie, Anyan; Harshe, Rasika; Cowan, Peter J; Csizmadia, Eva; Wu, Yan; Moss, Alan C; Chen, Ridong; Robson, Simon C; Longhi, Maria Serena
Abstract: Background and Aims: CD39/ENTPD1 scavenges pro-inflammatory nucleotides, to ultimately generate immunosuppressive adenosine, which has a central role in immune homeostasis. Global deletion of Cd39 increases susceptibility to experimental colitis while single nucleotide polymorphisms within the human CD39 promoter, and aberrant patterns of expression during experimental hypoxia, predispose to Crohn's disease. We aimed to define the impact of transgenic human CD39 [hTG] overexpression in experimental colitis and to model therapeutic effects using the recombinant apyrase APT102 in vivo . We also determined the in vitro effects of APT102 on phenotypic and functional properties of regulatory T-lymphocytes derived from patients with Crohn's disease. Methods: Colitis was induced by administration of dextran sulfate sodium in wild-type [WT] or hTG mice, and, in another model, by adoptive transfer of CD45RB high cells with or without WT or hTG regulatory T cells [Treg]. In additional experiments, mice were treated with APT102. The effects of APT102 on phenotype and function of Treg and type-1 regulatory T [Tr1] cells were also evaluated, after purification from peripheral blood and lamina propria of Crohn's disease patients [ n = 38]. Results: Overexpression of human CD39 attenuated experimental colitis and protected from the deleterious effects of systemic hypoxia, pharmacologically induced by deferoxamine. Administration of APT102 in vivo enhanced the beneficial effects of endogenous Cd39 boosted by the administration of the aryl hydrocarbon receptor [AhR] ligand unconjugated bilirubin [UCB]. Importantly, supplemental APT102 restored responsiveness to AhR stimulation by UCB in Treg and Tr1 cells, obtained from Crohn's disease patients. Conclusions: hCD39 overexpression ameliorated experimental colitis and prevented hypoxia-related damage in vivo . Exogenous administration of APT102 boosted AhR-mediated regulatory effects in vivo while enhancing Treg functions in Crohn's disease in vitro .